FORMATION OF A SET OF ACTIONS OF AUTHORITIES AND BUSINESS STRUCTURES THAT INFLUENCE FACTORS THAT HINDER THEIR INTERACTION WITHIN THE FRAMEWORK OF DIGITAL INTEGRATION - R. Ustaev; M. Ustaeva; O. Berezhnaya; O. Boris; G. Vorontsova; O. Momotova (Вестник Северо-Кавказского федерального университета)
The article substantiates the importance of studying the unresolved problems of interaction between authorities and business structures at the regional level within the digital economy. The ways of solving problems based on the previously analyzed results are proposed, which revealed both traditional negative factors and factors that form during the interaction of authorities and business structures at the regional level in the conditions of digitalization. A set of actions on the factors that hinder the interaction of authorities and business structures at the regional level within the digital economy is presented. Including in the implementation of targeted programs. The authors of the article propose a number of measures aimed at successfully improving the interaction of public authorities and business.